Pembelajaran Menganalisis Teks Prosedur dengan Menggunakan Model Problem Based Learning di Kelas 9 SMPN 2 Sukaluyu Cianjur (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2026)
Analyzing procedural texts is an essential competence in Indonesian language learning at the junior high school level, as it requires students to apply analytical thinking and understand textual structures systematically. However, in classroom practice, students often experience difficulties in identifying text structure, linguistic features, and communicative purposes of procedural texts. This study aims to describe the implementation of the Problem Based Learning model in teaching procedural text analysis to ninth-grade students at SMPN 2 Sukaluyu Cianjur and to examine its role in developing students’ analytical abilities. The research employed a qualitative descriptive approach involving students and an Indonesian language teacher as research subjects. Data were collected through classroom observation, analysis of students’ work, and documentation of learning activities. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings indicate that the implementation of Problem Based Learning increased students’ engagement in the learning process, encouraged active discussion and collaboration, and supported students in understanding and analyzing the structure and linguistic features of procedural texts more effectively. Students were not only able to comprehend procedural text concepts theoretically but also demonstrated the ability to apply analytical skills in evaluating and revising texts. The learning process became more meaningful as students actively constructed knowledge through problem-solving activities related to real-life contexts. The results of this study imply that Problem Based Learning can serve as an effective alternative instructional model for Indonesian language learning, particularly in fostering analytical skills, learner autonomy, and meaningful engagement in procedural text instruction at the junior high school level.